2016
DOI: 10.1038/srep30335
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxygen-deficiencies on Resistance Switching in Amorphous YFe0.5Cr0.5O3−d films

Abstract: Herein, we demonstrate the contribution of the oxygen-deficiencies on the bipolar resistance switching (RS) properties of amorphous-YFe0.5Cr0.5O3−d (a-YFCO) films. The a-YFCO films were prepared under various oxygen pressures to tune the concentration of oxygen-deficiencies in the films. The XPS data verify that the oxygen-deficiencies increase with decreasing oxygen pressure. The RS property becomes more pronounced with more oxygen-deficiencies in a-YFCO films. Based on the Ohmic conduction measurements in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The ten (10) successive loops of I -V characteristics were taken for both Au/In2O3/Si and Au/In2O3:Er/Si devices to investigate the state of defects present in the material. defects [28,29] into the lattice and at the Au/In2O3 Schottky interface. Under the forward bias condition, the undoped In2O3 TF produces ionisation due to the availability of huge free carriers (~8 x 10 16 cm -3 ) [4], which enhances the depletion width at the junction and finally charge storage of the device.…”
Section: Presence Of Memorymentioning
confidence: 99%
“…The ten (10) successive loops of I -V characteristics were taken for both Au/In2O3/Si and Au/In2O3:Er/Si devices to investigate the state of defects present in the material. defects [28,29] into the lattice and at the Au/In2O3 Schottky interface. Under the forward bias condition, the undoped In2O3 TF produces ionisation due to the availability of huge free carriers (~8 x 10 16 cm -3 ) [4], which enhances the depletion width at the junction and finally charge storage of the device.…”
Section: Presence Of Memorymentioning
confidence: 99%
“…With the further increase of revolution number, the localised corrosion is aggravated, but still weaker than as-cast sample, Figure 6c. In addition, the intergranular crack appear in the fractography of 2 turns sample, which can be attributed to hydrogen embrittlement [24], Figure 6d.…”
Section: Stress Corrosionmentioning
confidence: 98%
“…Previous studies have shown chitosan and collagen can lead to superior cell attachment because collagen is naturally found in ECM, and chitosan structurally resembles glycosaminoglycans (GAGs), a major component of ECM. [ 82,83 ] In particular, the Arg‐Gly‐Asp (RGD) binding sequences within the ECM mediates cell attachment. To better mimic the native microenvironment to improve cell‐biomaterial interactions, the use of natural polymers‐based scaffold and incorporation of ECM components into the biomaterial scaffold have emerged as promising strategies.…”
Section: Effect Of Scaffold Properties On Cellular Behaviormentioning
confidence: 99%